THE EFFECT OF (DMAA), DIMETHYLACETAMIDE ON THE BLOOD OF THE COWS IN VITRO - H. AL-Attia , H.; M. Jasim, Y. (The Iraqi Journal of Veterinary Medicine, 1988)
Dimethylacetamide (DMMA) is used as a solvent for drug preparations, DMAA and its metabolitesMonome thy lacetamide (MMAA) and acetamide (AA) cause hemolysis in concentrations above 100(DMAA), 44 (MMAA) and 40 (AA) mg/ml blood respectively. The effects are double to three timesstronger than after distilled water.Dimethylation in the animal body after treatment is followed by an increase of the hemolytic activity.Concentrations after therapeutic use in vivo are as high as the concentration in vitro in hemolysis activity.